Winter refuge for freshwater fish - Chemagin Andrey A. (E3S Web of Conferences, 2023)
The ecological aspect of the behavioral and physiological adaptation of fish in the autumn-winter period in water bodies of the temperate and subarctic climatic zones of the Northern Hemisphere is considered. It has been established that fish in the studied areas with a decrease in water temperature form aggregations in deep, low-speed sites for the successful wintering. In the considered period of the life cycle, the metabolism in fish slows down to reduce the depletion of lipid reserves; therefore, this group of aquatic organisms forms accumulations in areas with fundamental properties - depth and low flow rate. This phenomenon can be considered a behavioral-physiological adaptation developed as a result of evolutionary processes. The results of work on the discovery of such wintering grounds have been noted for the continents - Eurasia and North America. Fish families that use such winter refuge include Cyprinidae, Percidae, Coregonidae, Thymallidae, Salmonidae, Lotidae, Esocidae, Siluridae, and Acipenseridae.